Dan Christensen <Dan_Christensen@sympatico.ca> wrote in news:email@example.com:
>> 3^2 = (0^0)^2 = 0^(2*0) = 0^0 = 3 >> > > Good point! That's why I stipulate that a non-zero base for the Power > of a Power Rule (Theorem 5) which you use in your 2nd step.
Which is why you have nothing but contradictions here. You're asserting that 0^0 can be defined to be anything, and the exponent rules still work. They don't. However, if 0^0=0 or 0^0 =1, they do. Everyone on this group gets this point but you. You can't extend a definition without extending it.